Constancy of total protein contents in various regions of the feline central nervous system (Revista Española de Fisiología, 1976)
A striking constancy of total protein content was shown in 45 regions of the feline CNS, recognized as markedly heterogeneous. The hypophysis differed from these tissues, due perhaps to its high blood element content. Synaptosomal fractions prepared from 17 regions of the CNS did not exhibit this constancy.